Rupert takes a bath - Graham, Bob (Knoxfield Victoria, Australia : The Five Mile Press, 1986)
James learns quite a lot about water displacement when his dog, Rupert, unexpectedly joins him in the bathtub.
Keywords: Bath-Stories; Children's stories